(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article examines the dynamics of investments in fixed assets of the Russian Federation for the years 2010-2018, and analyzes the volume of investments in fixed assets in the Russian Federation. The basis for accelerating scientific and technological progress is investment in fixed assets, which is why for the modern market economy of the Russian Federation it is necessary to analyze and increase investment in fixed assets. The main goal of the study is to identify factors that influence the parameter in question.